2013
DOI: 10.1051/fruits/2013057
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Loranthaceae impact onVitellaria paradoxaC. F. Gaertn. fruit yield in contrasting habitats and implications for its conservation

Abstract: Variation of Loranthaceae impact on Vitellaria paradoxa C. F. Gaertn. fruit yield in contrasting habitats and implications for its conservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Research efforts have addressed issues of reproduction and management through tree nurseries [ 17 ], but the dissemination of such techniques is still lacking. In view of the improvements to the productivity and quality of shea tree resources, grafting trials were performed and showed potential to enhance the proliferation of desirable genotypes and reduce the length of the juvenile life stage[ 11 , 18 ], juvenile life stage that varies between 15 and 20 years under natural conditions. Fruit production typically commences at 20 years of age, but production is not maximized until 40 to 50 years of age[ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research efforts have addressed issues of reproduction and management through tree nurseries [ 17 ], but the dissemination of such techniques is still lacking. In view of the improvements to the productivity and quality of shea tree resources, grafting trials were performed and showed potential to enhance the proliferation of desirable genotypes and reduce the length of the juvenile life stage[ 11 , 18 ], juvenile life stage that varies between 15 and 20 years under natural conditions. Fruit production typically commences at 20 years of age, but production is not maximized until 40 to 50 years of age[ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fruits are harvested around May until September, coinciding with the rainy season [5]. The genetic variability of shea is noted to be high [7,8,[11][12][13][14] and there is no tradition of planting trees, as shea is highly effective in propagating itself in this environment. Recent work, however, with micro-propagation, rooting cuttings and grafting may allow opportunities to formally domesticate and enrich parklands through selection and planting of more productive shea trees [15][16][17][18].…”
Section: Shea Tree As a Traditional Crop And Domestic Commoditymentioning
confidence: 99%
“…Les travaux d 'Ondoua et al (2014) dans les cacaoyères du sud-Cameroun, de Fotso et al (2014) dans les jardins de case de l' Ouest-Cameroun, et ceux d'Azo'o et al (2013) dans les forêts de Lokomo, avaient quant à eux montré P. capitata comme espèce domminante. Toutefois, cette espèce est faiblement retrouvée en zone soudano-sahélienne dans les plantations d'agrumes, de karité, ou de Légumineuses (Soro et al, 2009 ;Houenon et al, 2012 ;Houéhanou et al, 2013). Les résultats observés indiqueraient que la zone d'étude remplirait les conditions climatiques favorables pour le développement d'H.…”
Section: Discussionunclassified